2017
DOI: 10.1186/s40345-017-0080-x
|View full text |Cite
|
Sign up to set email alerts
|

Lithium in the episode and suicide prophylaxis and in augmenting strategies in patients with unipolar depression

Abstract: BackgroundDepressive disorders are a leading cause of the global burden of disease and are associated with high recurrent often continuing morbidity and high excess mortality by suicide and cardiovascular disease. Whilst there are established, effective and cost-effective treatments for depression, their long-term management is often neglected: there is continuing controversy over the case of need for long-term treatment including lifelong treatment and safety issues.Objective and methodsIn this narrative revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 70 publications
1
29
0
4
Order By: Relevance
“…Since then, research into lithium's effects has established lithium as an effective treatment for bipolar disorder, both acutely and in maintenance treatment [2]. Moreover, it has been found effective in unipolar depression [3], and an anti-suicidal effect independent from its moodstabilizing properties has been suggested [4,5]. Finally, recent data have indicated a possible role for lithium in preventing mild cognitive impairment and dementia [6].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, research into lithium's effects has established lithium as an effective treatment for bipolar disorder, both acutely and in maintenance treatment [2]. Moreover, it has been found effective in unipolar depression [3], and an anti-suicidal effect independent from its moodstabilizing properties has been suggested [4,5]. Finally, recent data have indicated a possible role for lithium in preventing mild cognitive impairment and dementia [6].…”
Section: Introductionmentioning
confidence: 99%
“…Lithium is used in the treatment and prevention of mood episodes in patients with bipolar disorder (BD), as well as in an augmenting strategy in patients with treatment‐resistant depression . Adequate monitoring of lithium treatment is essential in order to assess, at the level of the individual patient, the balance between efficacy and side effects, and to adjust the treatment if necessary .…”
Section: Introductionmentioning
confidence: 99%
“…In spite of this, given that lithium is the only drug with evidence of efficacy in the prevention of both manic and depressive episodes in nonenriched study designs [10], the authors of both meta-analyses and accompanying commentaries [11,12] concluded that lithium should remain the standard treatment in the longterm management of bipolar disorders [4,5]. The evidence for lithium's unique antisuicidal properties as well as lithium's ability to control for subsyndromal symptoms further strengthen this view [13][14][15][16][17].…”
Section: Resultsmentioning
confidence: 99%